A Novel 14-Base-Pair Regulatory Element Is Essential for In Vivo Expression of Murine β4-Galactosyltransferase-I in Late Pachytene Spermatocytes and Round Spermatids - Charron, Martin (American Society for Microbiology, 1999)
During murine spermatogenesis, beginning in late pachytene spermatocytes, the β4-galactosyltransferase-I (β4GalT-I) gene is transcribed from a male germ cell-specific start site. We had shown previously that a 796-bp genomic fragment that flanks the germ cell start site and contains two putative CRE (cyclic AMP-responsive element)-like motifs directs correct male germ cell expression of the β-galactosidase reporter gene in late pachytene spermatocytes and round spermatids of transgenic mice (N. L. Shaper, A. Harduin-Lepers, and J. H. Shaper, J. Biol. Chem. 269:25165–25171, 1994). We now report that in vivo expression of β4GalT-I in developing male germ cells requires an essential and previously undescribed 14-bp regulatory element (5′-GCCGGTTTCCTAGA-3′) that is distinct from the two CRE-like sequences. This cis element is located 16 bp upstream of the germ cell-specific start site and binds a male germ cell protein that we have termed TASS-1 (transcriptional activator in late pachytene spermatocytes and round spermatids 1). The presence of the Ets signature binding motif 5′-GGAA-3′ on the bottom strand of the TASS-1 sequence (underlined sequence) suggests that TASS-1 is a novel member of the Ets family of transcription factors. Additional transgenic analyses established that an 87-bp genomic fragment containing the TASS-1 regulatory element was sufficient for correct germ cell-specific expression of the β-galactosidase reporter gene. Furthermore, when the TASS-1 motif was mutated by transversion, within the context of the original 796-bp fragment, transgene expression was reduced 12- to 35-fold in vivo.